Library Management (A Site Study at SD N Batursari 6 Mranggen Demak) - Sunarto, Sunarto (2011)
The objectives of this research are to describe (1) physical characteristic of school library at SDSN Batursari 6 Mranggen Demak, (2) service characteristic of school library at SDSN Batursari 6 Mranggen Demak. This research is qualitative research with ethnography design. This research is conducted in SDSN Batursari 6 Mranggen Demak. Human resources in this research are principal, library manager, teacher and students. Data collection method used depth interview, observation, and documentation. Data analysis with in case displays for describing stared (1) How Data Displays Work, (2) Partially Ordered Displays,(3) Time-Ordered Displays,(4)Role-Ordered Displays,and (5) Conceptually Ordered Displays. Data validity is consisting of credibility, transferability, dependability, and conformability. The research's result shows that (1) the width of library building is ore over 72 m2. The library is strategic and representative. Library consists of lobby room and central room that separated with collection room and reading room in one area (not separated). The facilities besides reading room that existing in library are computer, TV, CD, and AC. To accelerate learning activity student in library, the librarian made a lot of roles that should be obeyed by library visitor. (2) the circulation service consists of lending and returning service of book, registration of library member, pressing a claim of collection that is not returned, pressing of claim of fine and writing the visitor. Library services from Monday until Saturday. From Monday until Thursday are 07.00 until 13.00, in Friday 07.00 until 11.00, and on Saturday 07.00 until 12.00. The lend and return system of book library of teacher and employee is by automatic system (lend, return, and prolongation collection through computer facility) and open system (that is chosen by themselves to choose the book that will be lend) and close system. Book and reference counted 5.190 exemplars with various work and knowledge.